1971
DOI: 10.1126/science.173.3998.736
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activity and Synthesis of an Encephalitogenic Determinant

Abstract: A 45-residue fragment of the basic protein of myelin is encephalitogenic in the rabbit and monkey but relatively inactive in the guinea pig. Synthetic peptides containing the sequence of a tryptic peptide of the fragment Thr-Thr-His-Tyr-Gly-Ser-Leu-Pro-Gln-Lys are moderately encephalitogenic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…On the other hand, rabbits respond much more vigorously to these regions. Fragment 44-89 is a major encephalitogenic region when tested in rabbits [6,7,11,131 we extend previous studies concerning the encephalitogenic activity of the C-terminal region of the bovine protein when tested in rabbits. We present evidence that there are at least two different disease-inducing sites in this part of the protein localized within the sequences 134-150 and 154-170, respectively.…”
Section: Introductionsupporting
confidence: 74%
“…On the other hand, rabbits respond much more vigorously to these regions. Fragment 44-89 is a major encephalitogenic region when tested in rabbits [6,7,11,131 we extend previous studies concerning the encephalitogenic activity of the C-terminal region of the bovine protein when tested in rabbits. We present evidence that there are at least two different disease-inducing sites in this part of the protein localized within the sequences 134-150 and 154-170, respectively.…”
Section: Introductionsupporting
confidence: 74%
“…Third, the observed "cross reactivity" between region 1 -116 and 117-170 might depend on a similar "immunochemical" configuration of two sequences, one situated in region 1-90 and onc in 117-170, and thus does not, as hitherto supposed, reflect the presence of a common determinant in region 90-116. Shapira et al reported recently [7,38] the synthesis of a decapeptide which is encephalitogenic in rabbits. The stereochemical configuration of this peptide is said to show striking similarities to the previously synthesized tryptophan-containing region.…”
Section: Antigenic Determinants On Bovine Encephalitogenic Proteinmentioning
confidence: 99%
“…The encephalitogenic contribution of each of the amino acids from the tryptophan region, fswgaegqr, has been examined thoroughly in the guinea pig (8,29,37,43,44,47,50). The midpeptide, tthygslpqk, has been studied in the DR rat and rabbit (31,33). The hyperacute EAE site, pqksqrtqdenpv, has been analyzed in the Lewis rat (20-22, 45, 52).…”
Section: Methodsmentioning
confidence: 99%